170 Rapid deceleration and crash events in an RCT evaluating a safe transport program for older drivers. (1st September 2016) - Keay, Lisa; Coxon, Kristy; Chevalier, Anna; Clarke, Elizabeth; Rogers, Kris; Boufous, Soufiane; Ivers, Rebecca; Brown, Julie
Abstract : Background: Older drivers have increased crash involvement and vulnerability to injury. It was hypothesised that a one-on-one safe-transport program, designed to encourage planning for retirement from driving and self-regulation, could improve the safety of older drivers. Methods: The Behind the Wheel program (adapted from the KEYS® program) was evaluated using a randomised controlled trial involving 380 drivers aged 75 years and older, residing in the suburban outskirts of Sydney. The safety outcomes for this trial were >750 milli-g rapid deceleration events (RDE) and self-reported crashes. General linear models were used to model the impact of the program on the rate of RDEs and self-reported crashes, using distance travelled as an offset. Results: We recruited 380 participants (230 men) with an average age of 80 years and 366/380 (96%) completed the 12 month study. The program was delivered to 183/190 (96%) of drivers allocated to the intervention. In vehicle monitoring data was available for 351 participants (92%) for a median of 52 weeks [inter-quartile range (IQR) 44–52] and 5487 [IQR 3294–8641] km of travel. 218/351 (62%) drivers had at least one RDE and the median number of RDEs was 1 [IQR 0–4]. There was no between group difference in the rate of RDEs per distance driven (incident rate ratio (IRR) 0.85, 95% CI 0.61–1.18). Crashes were reported by 14 participants in the intervention and 19 in the control group (p = 0.46). Pre-planned sub-group analyses showed that the intervention was effective in significantly reducing RDEs (IRR 0.41, 95% CI 0.20–0.81), in drivers with a DriveSafe/DriveAware score of 96 or higher (fit to continue driving). Conclusions: Older drivers with good visual and cognitive function are responsive to a one-on-one education program to improve their safety on the road. These drivers reduced their involvement in RDE events by more than half, however this approach was not effective in drivers with poorer function.